Employee Satisfaction and Retention of Stanbic Bank Head Office in Accra, Ghana - Bertha Fiankobea Adjei; Verosivera Boateng; Jerry Anim; Oscar Opoku Agyemang; Benjamin Buabeng (HM Journals, 2022)
The study explores the organisational factors correlates that influence job satisfaction and employee retention. Specifically, the study examined the level of job satisfaction of the employees of Stanbic Bank; analyse the determinants of job satisfaction of the employees of stanbic Bank; examine the effect of job satisfaction on employee retention; and recommend istrategies that ican ibe used to improve ijob isatisfaction iand imaintain iemployee iretention iat the head office of Stanbic Bank. The study employed quantitative methodology. Data was collected through the administration of questionnaire to 130 employees of the bank. Moreover, ilinear iand imultiple iregression iwere iused ito iexamine ithe icause iand ieffect irelationship ibetween ijob isatisfaction iand iretention. It emerged from the study that better remuneration is the factor most considered by employees of Stanbic Bank Ghana’s head office to have the paramount influence on their satisfaction on job. Again, employees cited compensation as the factor to influence their retention or turnover, followed by career growth and development. It is recommended that Human Resource Managers strike a meaningful balance between compensation and opportunities for career advancement as these are the major turnover factors. Also, the management of the Stanbic Bank should improve upon their extrinsic motivations such as pay, promotions and reward since it really affects the job satisfaction of the employees.